Pengembangan Media Pembelajaran Video Animasi pada Materi Bangun Datar Kelas IV SD Negeri 104 Pekanbaru - Ivina Nur Ismi; Siti Quratul Ain (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine the feasibility of animated video learning media in the fourth grade flat building material at SD Negeri 104 Pekabaru. This research method uses development research with ADDIE development model. This research was conducted in three stages, namely 1) the analysis phase consisted of curriculum analysis, needs analysis, and student analysis; 2) the design stage, namely the design of animated video learning media using two applications, namely kinemaster and powtoon; 3) the development stage, namely producing learning media that have been designed in the design. In addition to media production, the researcher also developed a research instrument, namely a validation sheet. The results of this study indicate that the animated video learning media meets the very feasible criteria and the responses given by media experts are 94.16%, linguists are 85.41%, and material experts are 82.81%. Overall validation from media experts, linguists, and material experts with a percentage of 87.46% with a very decent category. The conclusion in this study is that the animated video learning media on the flat material is suitable for use in fourth grade elementary school learning. Keywords: Learning media, Animated video, Mathematics